(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In Uzbekistan today, more than 25 thousand women and 7 thousand men are diagnosed with infertility under dispensary observation. At the same time, the number of people who do not turn to doctors, according to experts, is much higher [9]. The problem of the relationship between reproductive function disorders and thyroid pathology is actively discussed in the scientific literature, since thyroid diseases are among the most common endocrinopathies in women of reproductive age [2, 3, 8]. Autoimmune thyroid diseases (AITD) - autoimmune thyroiditis (AIT), which is the main cause of hypothyroidism, and Graves’ disease (GD), which occurs with thyrotoxicosis, occur in approximately 5% of the world’s population and can lead to the development of pathology in the reproductive system of women in in the form of menstrual irregularities, infertility, miscarriage, pathology of fetal and newborn development [3, 4, 6, 7, 8]. Screening assessment of thyroid function has not been introduced into the practice of obstetricians, gynecologists and reproductive specialists. As is known, any strategy for screening and potential treatment of thyroid disorders in infertility must be based on objective data indicating the impact of these disorders on fertility. In this regard, it is necessary to clarify the frequency and structure of thyroid pathology in women with infertility and to assess the role of various types of thyroid pathology in the genesis of reproductive disorders.